Comparison between Effects of Fentanyl and Ketofol as Sedative in Elective Caesarean Section under Subarachnoid Anaesthesia (Delta Medical College Journal, 2020)
Background: Regional anaesthesia has become an important anaesthetic technique now a days. The use of spinal (subarachnoid) anaesthesia is often limited by the unwillingness of patients to remain awake during surgery. Pharmacologically induced tranquility improves acceptance of regional technique.Objective: This study compares Fentanyl and Ketofol (Ketamine+Propofol) in terms of onset and recovery of sedation, haemodynamic effects, respiratory effects and adverse effects of both the drugs during elective Caesarian section under spinal anaesthesia.Materials and method: This randomized clinical trial included 60 ASA (American Society of Anaesthesiologists) grade I patients between age 20-40 years undergoing elective Caesarean sections under subarachnoid anaesthesia during the period January 2022 to June 2022. Patients were randomly allocated to one of two groups: Fentanyl group (Group F, n=30), who received Fentanyl in a single dose of 0.5mcg/kg and Ketofol group (Group KP, n=30), who received Ketofol in a single dose of 0.5mg/kg (Ketamine-0.5mg/kg+ Propofol-0.5mg/kg). Spinal anaesthesia was conducted by injecting a hyperbaric solution of 0.5% bupivacaine 3ml through a 25G spinal needle at L3-4 level. All parameters were documented at 5 min intervals until arousal of the patient. The onset of sedation i.e. time from iv (intravenous) injection of Fentanyl or Ketofol to closure of eye lids (OAA/S score of 3) and the arousal time from sedation i.e. time from closing of the eye lids to OAA/S score of 5 ( patient is awake clinically) were noted. Any complication during operation was documented. The patient’s satisfaction with the sedation was assessed by the 5 point ‘Likert verbal rating scale.Results: There was no significant difference of mean blood pressure and mean heart rate between the two groups in different time intervals (p>0.05). Time of onset of sedation was significantly less with Ketofol than Fentanyl (p